SMART TOURISM THEORY AND A NEW CONCEPTUAL MODEL OF TOURISM SYSTEMS IN THE CONTEXT OF DIGITAL TRANSFORMATION - Khaitov Okhunjon Nomoz oglu (Modern American Journals, 2025)
This article provides an in-depth scientific analysis of the impact of the theory of smart tourism and the integration of digital transformation processes on modern tourism systems. The development of digital technologies - IoT, Big Data, artificial intelligence, cloud services, mobile applications, geolocation systems and digital experience platforms - is fundamentally changing the functional architecture of tourism systems, allowing them to be adaptive, transparent, flexible management, provide real-time services and create a highly personalized tourist experience. The article scientifically assesses the weaknesses of traditional tourism systems and proposes a conceptual model of a smart tourism ecosystem. This model is interpreted as an integrated management system of multi-vector information flows between tourists, service providers, state institutions and digital infrastructure. The results of the research create a methodological basis for the formation of new paradigms of smart tourism, as well as for the modernization of tourism systems in Uzbekistan and other developing countries in the context of a digital economy.